Redistributive politics in Russia: The political economy of agricultural subsidies - Vasyl Kvartiuk; Thomas Herzfeld (Comparative Economic Studies, 2021)
This paper explores whether redistributive politics can explain differences in agricultural subsidies in Russia, a country whose autocratic regime represents a fertile ground for strategic redistribution. Relying on political economy literature, we examine the strategies regional and federal Russian politicians utilize to allocate and distribute agricultural subsidies. Using unique 2008–2015 panel data, we test whether politicians target loyal or easily swayed voters and whether they use large farms as vote brokers. We find federal and regional politicians to allocate more agricultural subsidies when political competition against the dominant party is higher. Moreover, they appear to also target large farms for voter mobilization.
Keywords: D72; H77; H23; P16; 630; agricultural subsidies; redistribution; political competition; vote brokers; Russia